2017
DOI: 10.3390/min7090165
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Fly Ash Mixed Tailings Slurries and Applicability of Prediction Models

Abstract: Abstract:Coal fly ash has potential applications in the management of reactive mine tailings. The shear stress versus shear rate curves obtained during viscometer tests are presented to describe the rheological behaviors of tailings slurries mixed with fly ash. The investigation was conducted on specimens prepared with different fly ash additions as well as prepared at variable conditions of temperature, mixing time, and CaCl 2 solution. It was observed that the rheological properties of ash-tailings slurry mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Several models have been used to describe non-Newtonian behavior. 41,42,43,44,45 For construction materials, models such as Power law (Ostwald-deWaele), 36,44,45 Bingham and modified Bingham, 43,44,45,46,47 Herschel-Bulkley, 43,44,45,47 Casson, 43,44,45,47 Sisko, 43,45,46 De Kee, 43,44,47 and Carreau 45,48,49 (and many more) have been utilized. The Carreau model 50 has previously been shown to give the best prediction of non-Newtonian fluids of suspended solids.…”
Section: Analysis Of Shear Rate Dependent Viscositiesmentioning
confidence: 99%
“…Several models have been used to describe non-Newtonian behavior. 41,42,43,44,45 For construction materials, models such as Power law (Ostwald-deWaele), 36,44,45 Bingham and modified Bingham, 43,44,45,46,47 Herschel-Bulkley, 43,44,45,47 Casson, 43,44,45,47 Sisko, 43,45,46 De Kee, 43,44,47 and Carreau 45,48,49 (and many more) have been utilized. The Carreau model 50 has previously been shown to give the best prediction of non-Newtonian fluids of suspended solids.…”
Section: Analysis Of Shear Rate Dependent Viscositiesmentioning
confidence: 99%
“…Similar to dewatering, the rheology of tailings is often characterized using shear yield stress, apparent viscosities, and compressive yield stress . In all studies, tailings have a non‐Newtonian behaviour, and this is expected given the high solids concentrations.…”
Section: Rheology In Mineral Processing Unit Operationsmentioning
confidence: 99%
“…Figures [12][13][14][15][16][17] indicated that the bleeding ratio of all slurry samples decreased as the temperature increased. The magnitude curves of cement slurries without fly ash showed larger variation than that with fly ash.…”
Section: Resultsmentioning
confidence: 99%
“…Fly ash with activity and cement forms a stable cement body. Lee et al [12] presented that the increase of temperature resulted in lower shear stress of the slurry mixtures. At the same time, the differences of shear stresses showed less sensitivity at high temperatures, indicating that the high temperature accelerated the hydration of fly ash.…”
Section: Introductionmentioning
confidence: 99%